Study on the antibacterial effect on kalanchoe pinnata against coagulase negative staphylococcus (CNS) / Nor Syahira Yusoff - Yusoff, Nor Syahira (2017)
Staphylococcus epidermidis was characterized as coagulase negative staphylococcus (CNS) that have long been described as a nonpathogenic organism. The presence of enterotoxin and cytotoxin within this species give rise to it become potentially pathogenic and develop in infection. They frequently founded in bloodstream and significantly established as nosocomial agents. In veterinary field, Staphylococcus epidermidis was the among bacteria that frequently contribute to mastitis and among the highest number isolated from bovine milk. One of the famous medicinal plants used in this experiment is the Kalanchoe pinnata that positively contains antimicrobial compound; alkaloid and flavonoid. The aim of this study were to determine the secondary metabolites in crude extract of Kalanchoe pinnata and to determine the antimicrobial activity of Kalanchoe pinnata against CNS . The disc diffusion method was performed by using S.epidermidis , however there was no inhibition zone founded , then explained that this species was not sensitive towards K. pinnata below 100mg/ml..The increasing production of biofilm and protein in S. epidermidis explained these recent bacteria was survived in K.pinnata extract from the range of 12.5mg/ml until 100mg/ml.